A qualitative study of smokers' assessments of four smoking cessation interventions delivered in a hospital emergency department. (1st August 2022) - Grau, Lauretta E.; Jurczak, Elizabeth; Zahid, Mahrukh; Brooks, Avis Harper; Weiss, June; O'Leary, Teresa K.; Pham, Timothy; Bernstein, Steven L.
Abstract: Background: A recent clinical trial of 1056 adults who smoke tested the efficacy of four components of a treatment intervention initiated in a hospital emergency department (ED) and found two of them to be clinically effective. This paper explores study participants' attitudes towards the four components, whether they identified important interactions, and suggestions for further tailoring. Methods: Telephone interviews were conducted with participants at the end of the three-month study period. Each participant had received at least one intervention component: nicotine replacement therapy, referral to a smokers' telephone quitline, a brief negotiation interview, or the smartphone-enabled SmokefreeTXT program. Interviews were audio-recorded, transcribed, and analyzed using an iterative approach, grounded in the data, using thematic analysis. Results: Between March 2017 and September 2018, 63 interviews were conducted with participants who received at least one intervention component. The sample was diverse with respect to race, ethnicity, gender, and sociodemographic status. Intervention components were generally well-received by participants. Four themes were identified: Intervention Context, Intervention Content, Communications, and Recommendations. Provision of smoking cessation interventions to ED patients led to reduced self-reported smoking for most. Nicotine replacement therapy diminished cravings, while behavioral interventions provided social support that helped motivate and sustain behavior change. Conclusions: Intervention components were feasible and acceptable. The data suggest that pharmacological and behavioral interventions be offered simultaneously, that communication skills training be provided to those who deliver the interventions, and that interventions should respect participants' autonomy and preferences concerning intervention timing, frequency, and termination. Highlights: First Multiphase Optimization Strategy trial to integrate a qualitative component. Subjects considered EDs an appropriate setting for tobacco cessation interventions. Subjects wished to receive combination of behavioral and pharmacologic treatments. Subjects noted that interventions should be tailored to user preferences. Good communication skills are essential to intervention uptake.